Small Cell Neuroendocrine Carcinoma of the Cervix in Pregnancy: A Case Report and Review - Linglan Pan; Renyan Liu; Xiujie Sheng; Dunjin Chen (Case Reports in Obstetrics and Gynecology)
Small cell neuroendocrine carcinoma of the cervix is a rare subtype of cervical cancer. Here we report a case in which a 27-year-old female patient presented at 34-week gestation with abnormal vaginal bleeding, underwent normal labor, and gave birth to a healthy neonate. Her pregnancy was complicated with a cervical tumor which turned out to be small cell neuroendocrine cervical carcinoma. We reviewed and discussed the features, diagnosis, and prognosis of small cell neuroendocrine carcinoma of the cervix.